Advancing nursing practice with artificial intelligence: Enhancing preparedness for the future - Moustaq Karim Khan Rony; Mst. Rina Parvin; Silvia Ferdousi (Wiley, 2024)
Abstract Aim This article aimed to explore the role of AI in advancing nursing practice, focusing on its impact on readiness for the future. Design and Methods A position paper, the methodology comprises three key steps. First, a comprehensive literature search using specific keywords in reputable databases was conducted to gather current information on AI in nursing. Second, data extraction and synthesis from selected articles were performed. Finally, a thematic analysis identifies recurring themes to provide insights into AI's impact on future nursing practice. Results The findings highlight the transformative role of AI in advancing nursing practice and preparing nurses for the future, including enhancing nursing practice with AI, preparing nurses for the future (AI education and training) and associated, ethical considerations and challenges. AI‐enabled robotics and telehealth solutions expand the reach of nursing care, improving accessibility of healthcare services and remote monitoring capabilities of patients' health conditions.